PERANCANGAN PERALATAN PENGONGSENGAN BIJI KOPI SISTIM BLOWER (Design of Coffee Roaster Using Blower System) - Syarifuddin, Syarifuddin (Baristand Industri Banda Aceh, 2015)
Aceh is one of the largest coffee producer in Indonesia. In Aceh Province, coffee plantsgenerally grow in the region of Gayo highland (Aceh Tengah and Bener Meriah). Generally, coffeproducers in Aceh are still using simple processing tools to roast the coffee resulting black beans andcharred that can eliminate the distinctive taste of coffee. This research aims to design of coffee roaster byusing blower system with the following specifications: reactor capacity of 0,5 kg, cylinder reactordimension: length of 30 cm, diameter of Ã 20 cm and plate thickness 5 mm. The roaster itself had 80 cmlength,50 cm width and 120 cm height. The experiment was done under the variation of two variables: (a)in dependent variable: cylinder rotation speed 75 rpm, (b) dependent variables: processing temperature120, 130, 140 and 150 oC, roasting time 8, 9 10, 11 and 12 minutes and coffee weight 250, 300,400 and500 gr. The quality of coffee were analyzed on moisture content, colour, aroma and the infection of fungi.Results showed that the moisture conten coffee were low about 0,28 â 1, 76%. Fortunately the bestflavour, aroma and colour of coffee were obtained under the treatment of roasting time 10 minutes,processing temperature 130 0C as the flavor and aroma of coffee can be maintained. In addition, therewas no infection from fungi as well as mold at all treated samples.